What is the scope of practice of the nurse practitioner as a surgical assistant in Australia? - Toni Hains; Catherine Smith (Journal of Perioperative Nursing)
Discussion around the scope of practice of all nurse practitioners (NPs) in Australia was a component of the recent review of NPs’ eligibility to have broader access to the Medical Benefits Schedule (MBS). This review process has been prolonged and, while the MBS review officially concluded on the 30 June 2020, no information regarding decisions about expanded NP access to the MBS for patient rebates had been disclosed at the time of publication. It is anticipated that the MBS review will contribute little change to NP access to the MBS.